Scheduling for Massive MIMO using channel aiging under QoS constraints - Pham, Hung; Hoai, Bac Dang; Tien, Ban Nguyen (Vietnam Journal of Science and Technology, 2019)
Massive multiple-input multiple-output (MIMO) networks support QoS (Quality of Service) by adding a new sublayer Service Data Adaption Protocol on the top of Packet Data Convergence Protocol layer to map between QoS flows and data radio bearers. In downlink for Guaranteed Bit Rate (GBR) flows, the gNB guarantees the Guaranteed Flow Bit Rate (GFBR) that defines the minimum bit rate the QoS flow can provide. So, one of the most important requirements is the minimum rate. The channel aiging helps to improve the sum-rate of Massive MIMO systems by serving more users to increase the spatial multiplexing gain without incurring additional pilot overhead. In this paper, a novel scheduler, termed QoS-Aware scheduling, is designed and proposed for Massive MIMO to use the channel aiging to increase the sum-rate but guarantee the minimum bit rate per user to support QoS. We investigate how many users are enough to serve to maximize the sum-rate while keeping the data rate per user meeting a given threshold. Through the numerical analysis we confirmed that QoS-Aware scheduling can guarantee a minimum rate per user and get a higher useful through-put (goodput) than conventional channel aiging schedulers.